Comprehensive pan-cancer analysis reveals NTN1 as an immune infiltrate risk factor and its potential prognostic value in SKCM - Fuxiang Luan; Yuying Cui; Ruizhe Huang; Zhuojie Yang; Shishi Qiao (Scientific Reports)
Abstract Netrin-1 (NTN1) is a laminin-related secreted protein involved in axon guidance and cell migration. Previous research has established a significant connection between NTN1 and nervous system development. In recent years, mounting evidence indicates that NTN1 also plays a crucial role in tumorigenesis and tumor progression. For instance, inhibiting Netrin-1 has been shown to suppress tumor growth and epithelial-mesenchymal transition (EMT) characteristics in endometrial cancer. To further elucidate the influence of genes on tumors, we utilized a variety of machine learning techniques and found that NTN1 is strongly linked to multiple cancer types, suggesting it as a potential therapeutic target. This study aimed to elucidate the role of NTN1 in pan-cancer using multi-omics data and explore its potential as a prognostic biomarker in SKCM. Analysis of the TCGA, GTEx, and UALCAN databases revealed significant differences in NTN1 expression at both the mRNA and protein levels. Prognostic value was evaluated through univariate Cox regression and Kaplan–Meier methods. Mutation and methylation analyses were conducted using the cBioPortal and SMART databases. We identified genes interacting with and correlated to NTN1 through STRING and GEPIA2, respectively. Subsequently, we performed GO and KEGG enrichment analyses. The results suggested that NTN1 might be involved in crucial biological processes and pathways related to cancer development and progression, including cell adhesion, axon guidance, immune response, and various signaling pathways. We then explored the correlation between NTN1 and immune infiltration as well as immunotherapy using the ESTIMATE package, TIMER2.0, TISIDB, TIDE, TIMSO, and TCIA. The relationship between NTN1 and tumor heterogeneity, stemness, DNA methyltransferases, and MMR genes was also examined. Lastly, we constructed a nomogram based on NTN1 in SKCM and investigated its association with drug sensitivity. NTN1 expression was significantly associated with tumor immune infiltration, molecular subtypes, and clinicopathological features in various cancers. Genetic analysis revealed that Deep deletions were the most common type of NTN1 alteration. Additionally, a positive correlation was observed between NTN1 CNAs and its expression levels. In most cancers, NTN1 showed positive correlations with immune and stromal scores, as well as with specific immune cell populations. Its predictive value for immunotherapy response was comparable to that of tumor mutational burden. Furthermore, NTN1 exhibited positive correlations with tumor heterogeneity, stemness, DNA methyltransferase genes, and MMR genes. In SKCM, NTN1 was identified as an independent risk factor and demonstrated potential associations with multiple drugs. NTN1 exhibits substantial clinical utility as a prognostic marker and indicator of immune response across various tumor types. This comprehensive analysis provides insights into its potential implications in pan-cancer research.